Graphene sheet with periodic vacancy: A first principles study. (16th December 2021) - Maikhuri, Deepti; Parkash, Jai; Abbas, Haider
Abstract: We present a comprehensive first-principles study of the electronic structure of graphene sheet with periodic vacancy. We report the structural, electronic, and magnetic properties of the graphene sheet with periodic vacancy that possess 48 C & 28 H atoms. Computational analysis based on density functional theory predicts that the periodic vacancy can modulate the properties of graphene sheet. Results show that periodic vacancies lead to the manipulation of band gap & could be utilized to tailor the electronic properties of the sheet. Also, it is found that, the graphene sheet with periodic vacancy is non-magnetic in nature.